- 1-214-256-5804
- info@tutorpace.com

√(-4i) can be split further in order to simplify the expression.

This implies that √(-4) = √4 * √-1

Here, √4 can be written as √4 = √(2 * 2) = 2

Therefore, √4 = 2 and this gives √-4 = √4 * √-1 ==> √-4 = 2 * √-1.

And √-1 is equal to ‘i’ ==>√-4 = 2 * √-1 = 2 * i

Hence the value of the expression, √(-4) = 2i

√(-27) can be split further in order to simplify the expression.

This implies that √(-27) = √27 * √-1

Here, √27 can be written as √27 = √(3* 3 * 3) = 3√3.

Therefore, √27 = 3√3 and this gives √-27 = √27* √-1 ==> √-27 = 3√3* √-1.

And √-1 is equal to ‘i’ ==> √-27= 3√3 * √-1 = 3√3 * i

Hence the value of the expression, √(-27) = 3i√3.